Effects of Gas–Surface Interaction Conditions on the Performance of Knudsen Force-Based, Low-Pressure Micro Hydrogen Sensors - Yanli Wang; Xiaowei Wang; Chunlin Du; Zhijun Zhang (Micromachines)
Knudsen force phenomenon caused by non-uniform temperature fields in rarefied gas has been a topic of interest among researchers of gas sensing and structure actuating for micro-electromechanical systems (MEMS). The effects of gas–surface interaction conditions (accommodation coefficients, temperature differences, and carrier gases) on gas flows and hydrogen detection performance (Knudsen force) in MEMS gas sensors, consisting of a series of triangular cold beams and rectangular hot beams, are studied by using direct simulation Monte Carlo (DSMC) method combined with the Cercignani–Lampis–Lord (CLL) model in this work. The research results reveal that Knudsen force strongly depends on accommodation coefficients, temperature difference, and carrier gases. Specifically, the dependence of Knudsen force on accommodation coefficients is stronger at high pressure than at low pressure. In particular, Knudsen force increases slightly as accommodation coefficients are reduced from 1 to 0.1 but dramatically rises when accommodation coefficients verge on 0. In addition, Knudsen force is almost a linear function of temperature difference. The peak value of Knudsen force can be increased by roughly 28 times when the temperature difference rises from 10 K to 300 K. Last but not least, the linear correlation of hydrogen concentration in binary gas mixtures with Knudsen force is proposed for gas concentration detection in practice.